2019
DOI: 10.1177/0300891619839288
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability (between radiation oncologist and radiation therapist) in tumor bed contouring after breast-conserving surgery

Abstract: Purpose: To examine interobserver variability between the radiation oncologist (RTO) and the radiation therapist (RTT) in delineating the tumor bed (TB) in early breast cancer (BC). Methods: We retrospectively analyzed patients who received a radiotherapy boost to the TB. In a first group, the clinical target volume (CTV) for the boost was the surgical bed, defined by using surgical clips. In a second group, the CTV was defined by identifying a seroma cavity or a metallic find on the scar. These contours were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Countmaps of overlapping GTV and CTV-contours of all delineators were generated with voxel size 0.8 × 0.8 × 2 mm, in which interrater agreement per voxel is indicated by differences in color. We assessed volumetric differences in GTVs, CTVs and PTVs and calculated a Dice similarity coefficient (DSC) and conformity index (CI), also known as concordance index [5,14,18] for all study contours and the reference delineation in order to evaluate possible differences. Also, the generalized CI was determined [19], defined as the total of the common volumes between observer pairs divided by the total of the encompassing volumes between each observer pair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countmaps of overlapping GTV and CTV-contours of all delineators were generated with voxel size 0.8 × 0.8 × 2 mm, in which interrater agreement per voxel is indicated by differences in color. We assessed volumetric differences in GTVs, CTVs and PTVs and calculated a Dice similarity coefficient (DSC) and conformity index (CI), also known as concordance index [5,14,18] for all study contours and the reference delineation in order to evaluate possible differences. Also, the generalized CI was determined [19], defined as the total of the common volumes between observer pairs divided by the total of the encompassing volumes between each observer pair.…”
Section: Discussionmentioning
confidence: 99%
“…In the pretreatment phase organ-at-risk (OAR) delineations are often performed by RTTs [5]. Following adequate training, RTTs achieve a good concordance with OAR contoured by ROs [6].…”
Section: Introductionmentioning
confidence: 99%
“…The three most-reported outcomes from AP roles were: enhanced service capacity, higher patient satisfaction, and safety maintenance. Only two studies 101,128 reported negative outcomes.…”
Section: Evidence Related To the Impact Of Ap Rolesmentioning
confidence: 99%
“…The variability in CTV contouring for breast cancer patients between RO and RTT has been investigated in a small study with non-clinical data and was found to be low [5]. It has also been shown that with appropriate training, the RTT has a high potential to complete the tumor bed contouring after breastconserving surgery with the use of clips, as part of the multidisciplinary radiotherapy team [6]. By delegating the task of delineation from the RO/PA to the RTT, the planning process is expected to become more time efficient.…”
Section: Introductionmentioning
confidence: 99%